Landscapes and soils of North Sea barrier islands: a comparative analysis of the old West and young East of Spiekeroog Island (Germany) - Pollmann, Thomas; Junge, Birte; Giani, Luise (ERDKUNDE, 2018)
To get further insights into the development of landscape elements and soils of North Sea barrier islands; an old part in the West (formed between approx. 1650-1860) and a young part, largely unaffected by anthropogenic influences in the East (formed approx. 1960), of the island Spiekeroog were comparatively analyzed. Between the two parts beach soils (World Reference Base of Soil Resources (WRB), IWG WRB (2015): Eutric Fluvic Tiadalic and Eutric Endosalic Arenosols; German Soil Classification System (GSCS), Ad-hoc-AG Boden (2005): Nassstrand and Strand) did not differ, except for microbial mats, which were found only in the East. In the West, a dune complex comprising white, gray and brown dunes holds a soil chronosequence from unaltered sands (WRB: Eutric Protic Arenosol; GSCS: Lockersyrosem) to braunified and podzolized soils (WRB: Dystric Brunic Arenosol; GSCS: Braunerde). However, in the East, only a single white dune chain, with adjacent shallow dune mounds to the south, had formed. In both parts, dune slacks evinced remarkably rapid peat formation (WRB: Dystric Histic and Eutric Histic Gleysols; GSCS: Niedermoorgleye). Here, iron content of groundwaters determined the formation of redoximorphic features. Soils of the salt marshes (WRB: Eutric Fluvic and Eutric Gleysols; GSCS: Rohmarschen) showed the highest contents of soil organic carbon (SOC) in the West, where the thickest fine sediment layers were also found. Revealed shortcomings of the German soil classification system concerning the classification of ‘Strand’ and ‘Rohmarsch’ soils are discussed. It is suggested to exclude the obligatory carbonate (CaCO3) content in the definition of the Strand soil and to introduce an additional horizon prefix to indicate carbonate contents between > 0 and < 2 %, in order to classify Rohmarsch soils, with primary carbonate contents < 2 %. Finally, an outlook on the future landscape -and soil development is provided, which is expected to be most profound in the young East.